Základní ukazatele charakterizující acidobazickou rovnováhu organismu a její poruchy - Kubát, K (Vnitrni lekarstvi, 1996)
The author describes and evaluates basic parameters used for evaluation of the acid-base balance: pH, pCO2, BE, BBS, (Na + K)/Cl, (AG) and RA. He compares the theories of two basic schools, the Copenhagen and Boston school and synthesizes the different views of various authors. A combination of modern theories permits to evaluate simple and combined disorders of the acid-base balance, disorders which can potentiate each other but also mask their effect. The author mentions also the importance of oxygen parameters and of other substances essential for obtaining energy, the importance of assessment of the patient's clinical condition, the necessity of retrospective evaluation based on the trend of changes of the acid-base balance in the course of time. In the article mathematical logical terminology of acid-base balance disorders is used, the attached figures and calculations facilitate the understanding of this pretentious problem.
Keywords: Acid-Base Imbalance; poruchy acidobazické rovnováhy; Carbon Dioxide; Acid-Base Equilibrium; Anions; anionty; Humans; acidobazická rovnováha; Hydrogen-Ion Concentration; lidé; oxid uhličitý; koncentrace vodíkových iontů